2002
DOI: 10.1037/0735-7028.33.3.330
|View full text |Cite
|
Sign up to set email alerts
|

The role of language in training psychologists to work with Hispanic clients.

Abstract: The increasing number of Spanish and English bilingual and Spanish-dominant clients requesting psychological services creates challenges for practitioners and agencies. Literature regarding the importance of the Spanish language in providing service to Hispanic clients is reviewed. It is argued that services to Spanish-speaking clients are frequently inadequate because of the lack of training in the use of Spanish in professional settings. A model for training psychologists to provide psychological services in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
54
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 28 publications
(44 reference statements)
13
54
0
Order By: Relevance
“…These findings support those of other researchers (Biever et al, 2002;Verdinelli & Biever, 2009) who stated that even though there are bilingual counselors possibly capable of providing services to LEP clients, these counselors may be hesitant to do so because of a lack of training. Most of the participants highlighted the need for counseling programs to provide training opportunities for students to practice their bilingual language skills (speaking, reading, and writing).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These findings support those of other researchers (Biever et al, 2002;Verdinelli & Biever, 2009) who stated that even though there are bilingual counselors possibly capable of providing services to LEP clients, these counselors may be hesitant to do so because of a lack of training. Most of the participants highlighted the need for counseling programs to provide training opportunities for students to practice their bilingual language skills (speaking, reading, and writing).…”
Section: Discussionsupporting
confidence: 82%
“…Instead, they reported learning "to provide services to Spanish-speaking clients through trial and error or by studying and researching the subject on their own" (Verdinelli & Biever, 2009, p. 236). This is similar to results reported by Biever et al (2002) and Rivas, Delgado-Romero and Ozambela (2005), in which participants reported self-training and limited bilingual supervision opportunities. Also, similar to Biever et al (2002), participants in Verdinelli and Biever's (2009) study indicated that formal training, such as content courses and clinical supervision specific to bilingual services, would be helpful.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Although there are relatively few mental health counselors with adequate linguistic skills to serve the LEP population, those who are bilingual and potentially capable of providing these services to LEP clients are often reticent to do so, possibly because they lack training in providing counseling services in languages other than English (Biever et al, 2002;Verdinelli & Biever, 2009). These data underscore the need for counseling programs that attend to the training and supervision of bilingual mental health counseling students-students who have the foundational linguistic abilities to provide counseling services to this growing LEP population.…”
Section: Discussionmentioning
confidence: 99%